VISUALISASI PRODUK KOSMETIK DALAM FOTOGRAFI KOMERSIAL - Eric Adam Brahmandita; Cokorda Istri Puspawati Nindhia; I Made Bayu Pramana (Retina Jurnal Fotografi, 2022)
The author visualizes cosmetic products into commercial photos. Commercial photos are photos that have a selling value and commercial photography is made according to commercial purposes, for example for advertisements of a product, for posters, or others. The concept raised by the author composes the Natural Creative theme that utilizes creative ideas from the author in order to produce interesting photos by utilizing natural concepts through light, color, and the technique of taking each photo. In this work, there are several applications of concepts, accessories and lighting formed by the method used by the author, some examples such as methods of exploration, experimentation, creation of works to finishing. Experimentation makes the source of exploration practicable through the materials used by the author so that it can proceed to the stage of forming the work. The stage of making the author's work tries to apply what has previously been conceptualized through exploration and experimentation. The author tries to sort out the works that have been shaped through the method and determine some of the best photos which will then enter the editing or editing stage. The work appointed by the author is the experience and guidance during an Independent Study/Project at SP Digital Marketing Agency. The author wants the work created in the future can be used to make teachings and fulfill the need for promotion of a product to promote producers who make interest to buy the product.